Web accessibility and usability evaluation methodology for people with Down syndrome - Alonso-Virgós, Lucía; Rodríguez Baena, Luis; González-Crespo, Rubén (Iberian Conference on Information Systems and Technologies, CISTI, 2020)
This work describes the methodological process carried out during an investigation that aimed to publish a list of useful web accessibility and usability guidelines and recommendations for users with Down syndrome. The division of the article is as follows: 1) First, a brief state of the art is offered where the main objective of the research is summarized, and the methods used in it are highlighted. These methods are interviews, user tests, and eye-tracking tests. It is intended to justify the importance of the correct application of these methods and their relevance during data extraction. 2) Next, each of the methods is detailed, explaining the set of rational procedures used to achieve the objective. This explanation is supported by bibliographic references of recognized prestige and other alternative research techniques, such as interviews with experts. 3) Finally, a set of conclusions and good practices is outlined that can be used for research that aims to work with participants who share similarities with those of this study. © 2020 AISTI.
Metodología de evaluación de accesibilidad y usabilidad web con personas con síndrome de Down
Ponencia de la conferencia "15th Iberian Conference on Information Systems and Technologies, CISTI 2020; Seville; Spain; 24 June 2020 through 27 June 2020"
Keywords: Down’s Syndrome; accessibility; usability; web; Scopus(2); WOS(2)